Duration of use of oral cannabis extract in a cohort of pediatric epilepsy patients. (18th November 2016) - Treat, Lauren; Chapman, Kevin E.; Colborn, Kathryn L.; Knupp, Kelly G.
Summary: Objective: Oral cannabis extracts (OCEs) are being used in the treatment of epilepsy with increasing rates in the United States following product legalization; however, no studies demonstrate clear efficacy. We evaluated the duration of use of OCEs as a measure of perceived benefit in a cohort of patients with pediatric epilepsy. Methods: Retrospective chart review was performed of children and adolescents who were given OCEs for treatment of epilepsy. Results: Of the 119 patients included in the analysis, 71% terminated use of their OCE product during the study period. The average length of use of OCE was 11.7 months (range 0.3–57 months). Perceived seizure benefit was the only factor associated with longer duration of treatment with OCE (p < 0.01). Relocation to Colorado was associated with perceived benefit of OCEs for seizures (65% vs. 38%, p = 0.01), but was not independently associated with longer OCE use. Factors associated with shorter use included adverse effects (p = 0.03) and a diagnosis of Dravet syndrome (p = 0.02). Twenty‐four percent of patients were considered OCE responders, which was defined by a parent's report of a > 50% reduction in seizures while on this therapy. Adverse events (AEs) were reported in 19% of patients, with the most common side effects being somnolence and worsening of seizures. Significance: Parental report of OCE use in refractory pediatric epilepsy suggests that some families perceive benefit from this therapy; however, discontinuation of these products is common. Duration appears to be affected by logical factors, such as perceived benefit and side effect profile. Surprisingly, families of patients with Dravet syndrome terminated use of OCEs more quickly than patients with other epilepsy syndromes. Results from this study highlight the need for rigorous clinical studies to characterize the efficacy and safety of OCEs, which can inform discussions with patients and families.